The business of tourism - Holloway, J. Christopher (Prentice-Hall, 2002)
An invaluable foundation book for Tourism or Tourism Management students, Holloway et al offers historical context, background theory and current research, making it possible for students to see how the industry has developed and to contextualise the current issues and challenges that Tourism is facing today. Holloway et al place emphasis on the practical operational aspects of the tourism industry, making this book well-suited to students who intend to one day work in Tourism.